Strategi Partai Keadilan Sejahtera Kota Padang dalam Memenangkan Pemilu Legislatif 2004 - S, Nurman; Rafni, Al (Jurnal Demokrasi, 2005)
This research focuses on PKSâ€™sÂ  strategy to win the election in terms of segmentation strategy, targeting, and establishing position. The problem is:â€œhow is PKS, dealing with opportunity and treat, win the election in terms of internal and external contextâ€?. Data was collected through depth interview and analyzed using Miles and Huberman models. The finding of the research showed that in terms of segmentation strategy, PKS focus onÂ  five communities segmentation, those are;Â  1) group of modern and educated peoples,Â  2) group of community fishermen, 3)Â  groups of farmer on the villages, 4) young educated peoples whoâ€™s participated in the reform period, and 5) group of women as active voters. From all of segmentations, PKS focuses on young educated peoples as their targeting party, while in terms of positioning strategy, PKS stated it self as dakwah and reform party. PKS opportunity in general election in 2009 relates to three dominant factors, that are; 1) partyâ€™s image 2), recruitment member system and 3) Minangkabau society culture. On the other hand, PKS treat relate to 1) Partyâ€™s commitment, 2) realignment and 3) funding. Â  Kata Kunci : Pemilu legislative, Partai Keadilan Sejahtera (PKS), strategi segmentasi,Â Â Â Â  peluang dan tantanga